What is for dinner? Qualitative and quantitative data regarding small mammal species identified in pellets of long-eared owl (Asio otus) from Cluj-Napoca - Ana-Maria NEACĂ; Anca-Ioana MARGEA; Alexandru N. STERMIN (Studia Universitatis Babeș-Bolyai. Biologia)
Analysis of pellets provides information on the prey distribution, abundance, behavior and trophic relationships between Strigiformes and small mammals. By analyzing the skulls from long-eared owl (Asio otus) pellets, collected from a colony located in the Mercur Park, in Cluj-Napoca, Romania, we aimed to identify the small mammal species and to compare the results with available ones from another study conducted 2 years ago in the same area. During 7 collecting campaigns (November 2018 to March 2019) in 538 pellets a total of 1290 skulls were identified. Over the study period, the colony increased from 10 to 40 birds. Six species of small mammals were identified: the field striped mouse (Apodemus agrarius), the yellow-necked mouse (Apodemus flavicollis), the wood mouse (Apodemus sylvaticus), the European water vole (Arvicola terrestris), the field vole (Microtus agrestis) and the common vole (Microtus arvalis). Compared with the previously study, a new species was identified: the yellow-necked mouse and another one was missing: the bank vole (Myodes glareolus).